A direct preset method for solving ease-off tooth surface of spiral bevel gear. (January 2023) - Chen, Peng; Wang, Sanmin; Li, Fei; Zou, Haoran
Abstract: In order to realize the global integrated control of spiral bevel gear tooth surface, this paper presents a direct preset method for solving ease-off tooth surface of spiral bevel gear. This method integrates the preset contact path (CP), geometric transmission error (TE) and curvature of difference curve at the contact point (CDC), which is called CPTE-CDC. Based on the relationship between ease-off and tooth surface planning grid, CPTE-CDC is used to establish a nonlinear overdetermined equations to solve ease-off surface equation. According to the ease-off surface obtained from the solution, the ease-off target tooth surface of pinion related to cuttting parameters is established, and its optimal machining parameters are solved based on Levenberg–Marquardt (LM) algorithm. Finally, a numerical example is created using TCA and LTCA techniques. The results show that the tooth surface obtained by CPTE-CDC method not only meets the preset contact characteristics, but also meets the design requirements, which proves the correctness of the proposed method. CPTE-CDC method can be used as a theoretical basis for improving the global control of spiral bevel gear tooth surface. Highlights: Establish ease off reference tooth surface through conjugate coordinate system. Forming a functional relationship between ease-off and planning coordinates. By CPTE-CDC method, solving nonlinear equations of ease-off function. Establishing ease-off target tooth surface, solved by LM.